Pertubuhan dan penggunaan laman web perniagaan di Malaysia - Ngu,, Betty Cheh Ing (Universiti Malaysia Sarawak, 2003)
The research aims to investigate the growth and the use of website in Malaysia businesses which mainly about e-commerce. All together 210 websites were choosing to observation in this research.